RANCANG BANGUN TRAINER ALAT PEMANAS AIR DENGAN ENERGI MATAHARI BERBANTUAN POMPA PANAS UNTUK MOTIVASI BELAJAR MAHASISWA - Yona, Teguh Irawan; Anshari, Khairul (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2026)
Solar energy is at the heart of efforts to diversify global energy sources due to its abundant potential worldwide. The purpose of this study is to discuss several strategies for utilizing solar energy. Thermal analysis to analyze the performance of water heaters has not yet been available. The working principle of a solar water heater is to heat water with solar energy. Students involved in the study will be asked to fill out a motivational questionnaire before and after using the Trainer for a solar water heater with the help of a heat pump. Data from this questionnaire will be analyzed by looking at the improvement from before and after by looking at the gain score value. The results of this study provide a significant contribution in strengthening similar research in the field of energy conversion learning. By focusing on the development of a Trainer for a solar water heater with the help of a heat pump that integrates innovative design methods, this study confirms that a holistic approach to energy conversion learning can effectively increase student learning motivation.